2017
DOI: 10.1007/s10876-017-1267-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biosynthesis of Gold Nanoparticles Using Salmonella enterica subsp. enterica serovar Typhi Isolated from Blood and Stool Specimens of Patients

Abstract: Salmonella is one of the most common causes of gastroenteritis. In this study, a PCR assay was developed for the rapid detection of microbial cultures of Salmonella enterica sub species of enterica serovar Typhi in samples of patients suspected typhoid. The assay was based on duplicate the STY4669-hypothetical protein gene. The gene primers were designed and blast. Then the bacteria strains were employed for the green synthesis of gold nanoparticles (AuNPs), and one of the strains represented ability to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The synthesis of nanoparticles was confirmed by a wavelength scan (300-700 nm) of the nanoparticles suspension. From previous studies, it has been suggested that the spectra in the 500-600 nm range correspond to AuNPs and in 350-500 nm range corresponds to AgNPs [34,35]. Both, AuNPs and AgNPs were scanned directly in suspension and with purified nanoparticles (Figure 1(A-D)) [18].…”
Section: Green Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…The synthesis of nanoparticles was confirmed by a wavelength scan (300-700 nm) of the nanoparticles suspension. From previous studies, it has been suggested that the spectra in the 500-600 nm range correspond to AuNPs and in 350-500 nm range corresponds to AgNPs [34,35]. Both, AuNPs and AgNPs were scanned directly in suspension and with purified nanoparticles (Figure 1(A-D)) [18].…”
Section: Green Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…During the synthesis of nanoparticles biomolecule, microbial biomass, fungi, plants or their derivatives (biosynthesis) act as both reducing and stabilizing agents of synthesized nanoparticles (33)(34)(35). These reactions can be considered as a green chemistry process that can minimize the environmental hazards in the chemical synthesis processes (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…. Biosafety issues should be considered in microbiological work as well as large-scale nanoparticle microorganisms and in commercial applications (33). .…”
Section: Introductionmentioning
confidence: 99%
“…17 The biosynthesis of nanoparticles using natural resources is a modern method with a lower expense and reduced pollution compared to previous methods. [18][19][20][21][22][23][24][25][26][27][28] Salvadora Persica (Salvadoraceae) is a tree with 6-7 m height, and its bark is cracked and wrinkled. It is an indigenous tree of the Middle East, Asia and Africa that commonly grows on the path of ooding and river bank.…”
Section: Introductionmentioning
confidence: 99%